Development of cross flow turbine with diffuser for hydrokinetic energy harnessing - Muhammad Alif Rasydan, Ruhatan (2022)
This project emphasizes the hydrokinetic energy energy harvesting device. Alternatively, the use of this turbine system can be converted kinetic energy of water to generate electricity. This project focuses on a device independent system to easily configure it. Therefore, several keys stand out in terms of size and potential power drain for the proposed device. The fluctuating characteristics of the water speed are also the challenges to be considered. In this thesis, the design of a cross-flow turbine with the device housing and blade and the raw energy used by the alternator is explained to develop a hydrokinetic energy harvesting device. The development of the device implements the use of SolidWorks software for design and manufacturing through to the assembly process, while incorporating multiple value creation processes along the way. The results show the effects of speed on the generated voltage and the effects of load on the AC generator.